PENGARUH KUALITAS LAYANAN, HARGA, PROMOSI TERHADAP KEPUASAN WISATAWAN DAN MINAT KUNJUNGAN KEMBALI (Studi pada Pengunjung Objek Wisata Air Owabong Kabupaten Purbalingga) - Ari Ardi Susanto; Tri Septin Muji Rahayu (Media Ekonomi, 2017)
The study aims to determine the effect of service quality, price, promotion variables to tourist satisfaction and interests to revisit. The researcher collected the samples by distributing questionnaires to respondents thought survey method. The sampling technique applied wa purposive sampling. The total samples were 96 respondents. IBM SPSS Statistics 21 applied to analyze the data. The analysis tools applied were validity test, reliability tast, classic assumption test, multiple linear regression analysis and simple linear regression. The partial test (t test) proves that the quality of service, price and promotion significanty affected the tourist satisfaction and tourist satisfaction significantly affected the interest to come back. The simultaneous test (f test) indicated that the service quality, price and promotion significantly affected tourist satisfaction.